Going Places: Travel Seminars as Opportunities for Interfaith Education - Mikoski, Gordon S. (Teaching theology and religion, 2013)
Many theological schools use short term travel as a way to foster interfaith education. Due to their experiential, holistic, and intense nature, travel seminars focused on the promotion of interfaith learning can shape a future religious leader's outlook on religious communities across the course of her entire career. In this article I explore the pedagogical dimensions of travel seminars as a tool for interfaith education through the lens of a travel seminar to Israel and the occupied Palestinian Territories.